2018
DOI: 10.1021/acs.langmuir.8b01279
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat-Induced Flocculation of Myosin-Based Emulsions through Steric Repulsion by Conformational Adaptation-Enhanced Interfacial Protein with an Alkaline pH-Shifting-Driven Method

Abstract: Protein conformational rearrangement triggered by adsorption to the hydrophobic interface of oil droplets has long been considered as a key factor in emulsification. In this study, an alkaline pH-shifting-driven conformational adaptation enhanced interfacial proteins was used to improve their stability against heat-induced flocculation of myosin emulsions. We used the unfolded myosin at pH 12 to emulsify soy oil and then readjusted the pH of the emulsion to neutral. The corresponding myosin emulsion (0.5% w/v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To ensure complete dissolution, different concentrations of TPP (0, 0.01%, 0.03%, and 0.05% (w/w)) were added to the soy oil and heated at 80 • C for 4 min [18]. O/W emulsions stabilized by MP were prepared according to the method of Li [19]. In brief, 10 g of soy oil with TPP and 90 g of MP solution were mixed with a homogenizer (Ultra Turrax T25 BASIS, IKA, Staufen im Breisgau, Germany).…”
Section: Preparation Of Mp-stabilized Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure complete dissolution, different concentrations of TPP (0, 0.01%, 0.03%, and 0.05% (w/w)) were added to the soy oil and heated at 80 • C for 4 min [18]. O/W emulsions stabilized by MP were prepared according to the method of Li [19]. In brief, 10 g of soy oil with TPP and 90 g of MP solution were mixed with a homogenizer (Ultra Turrax T25 BASIS, IKA, Staufen im Breisgau, Germany).…”
Section: Preparation Of Mp-stabilized Emulsionsmentioning
confidence: 99%
“…The droplet surface average sizes of emulsions were measured according to our previously reported method [19] using a Malvern Mastersizer 3000 (Malvern Instruments Ltd., Malvern, Worcestershire, UK). The refractive indexes of the dispersed phase (soy oil) and dispersant medium were 1.456 and 1.33, respectively.…”
Section: Droplet Surface Average Size (D 32 )mentioning
confidence: 99%
“…Since emulsions and foams are thermodynamically unstable, they typically require an amphiphilic stabilizer, such as a traditional molecular surfactant, particles, and block copolymers ,, or amphiphilic (homo)­polymers. They are summarized in Tables and . They adsorb to the interface/surface and are believed to stabilize the interface/surface through either electrostatic repulsion or steric repulsion. However, the exact mechanism of how they protect droplets and bubbles and what kind of properties are needed is not clear, because destabilizing processes are not static, but highly dynamic. Coalescenceone of the main destabilizing mechanisms of emulsionsis a representative dynamic process in which two droplets approach one another while the fluid in between them drains out, applying stress to the droplet interface .…”
Section: Stabilizersmentioning
confidence: 99%
“…Pezeshk et al [6] obtained optimal modification of shrimp by-products at a pH of 12.5. Li et al [7] indicated that treatment at pH 12 significantly improved the solubility and emulsification of myosin compared to pH 9, 10, and 11. Such an increase in pH values, on the one hand, contradicts green processing principles, and on the other hand, it could facilitate the formation of covalent bonds among MPs, leading to protein aggregation [4].…”
Section: Introductionmentioning
confidence: 99%